T − W relation and free energy of the Heisenberg chain at a finite temperature - Pengcheng Lu; Yi Qiao; Junpeng Cao; Wen-Li Yang; Kang jie Shi; Yupeng Wang (Journal of High Energy Physics, 2021)
Abstract A new nonlinear integral equation (NLIE) describing the thermodynamics of the Heisenberg spin chain is derived based on the t − W relation of the quantum transfer matrices. The free energy of the system in a magnetic field is thus obtained by solving the NLIE. This method can be generalized to other lattice quantum integrable models. Taking the SU(3)-invariant quantum spin chain as an example, we construct the corre- sponding NLIEs and compute the free energy. The present results coincide exactly with those obtained via other methods previously.